Analysis of Work Ability on Employee Performance at Furusato Izakaya Central Jakarta - Oktapine, Pilda; Kurniawan, Prasetyo (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the influence of work skills on employee performance at Furusato Izakaya, Central Jakarta. The study was conducted qualitatively and descriptively using interview, observation, and documentation techniques. The focus of the study included technical competency, work experience, and communication skills. The results indicate that understanding operational standards, work motivation, and experience in the restaurant industry significantly influence performance improvement, particularly in terms of service quality and punctuality. However, technical training and foreign language proficiency remain weaknesses that need to be addressed. This study recommends strengthening training and reward systems to support the continuous development of work skills.